The impact of Eskoba®, a glyphosate formulation, on the freshwater plankton community - Reno, Ulises (2014)
This study analyzed the acute effects of a glyphosate‐based herbicide (Eskoba®) on the microalgae Chlorella vulgaris, the cladoceran Simocephalus vetulus, and the copepod Notodiaptomus conifer, and evaluated the recovery ability of the surviving microcrustaceans. Survival, age of first reproduction, and fecundity were used as endpoints for S. vetulus, while survival and time to reach the adult stage were used as endpoints for N. conifer. The registered order of sensitivity was S. vetulus (48‐hour effective concentration [EC50]: 21 mg/L) > C. vulgaris (72‐hour EC50: 58.59 mg/ L) > N. conifer (48‐hour EC50: 95 mg/L). Despite the growth of C. vulgaris stimulated after 24 hours of exposure to the commercial formulation of glyphosate Eskoba®, it was inhibited after 48 hours by all the concentrations tested. In postexposure experiments, microcrustaceans reduced their life expectancy, S. vetulus decreased its fertility, and N. conifer inhibited its sexual maturity. In summary, it was demonstrated that these species lost their recovery ability.